PROBLEMS OF WOMEN WITH HIGH RISK OF ABANDONMENT OF A NEWBORN - Liakh, Tetiana; Hevchuk, Nataliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The research focuses on the identification of types of social and preventive work with women in women's consultations and maternity clinics to prevent abandonment of a newborn. The purpose of the research is to identify typical problems and needs of mothers in risk of abandoning a newborn. In the article, authors describe results of in-depth interviews of mothers who have been, or are at high risk of abandoning a newborn. Identified problems authors grouped into two main groups: psychological and social problems. In addition, the authors conducted a series of focus groups with health workers in delivery departments and women’s consultations, and as a result - suggested a categorization of factors influencing on abandoning a child in the first two years. These factors were grouped by the authors into two main categories: “personal” and “reference” factors. Further, based on expert survey of social workers, the authors developed recommendations for providing various social and preventive services to mothers who are willing to abandon a child. Developed recommendations reflect the following types of support: psychological support, social-pedagogical support, medical support and rehabilitation.